Distribution, Methodological Validation And Ecology Of Nocturnal Island Mammals In Peninsular Malaysia - Miard, Priscillia (2020)
Nocturnal research has developed in recent years, shining more light on the elusive animals that are active at night, and their behaviours. However, more efficient survey designs for nocturnal mammals according to their specific biological needs should be developed, as the commonly used artificial white light harms animals’ eyesight. Therefore, this study was aimed to test different detection methods by using different types of light to spot nocturnal, non-volant mammals and to assess their diversity, distribution and abundance in selected localities in Northern Peninsula Malaysia. Three main species were focused on; Sunda slow lorises (Nycticebus coucang), red giant flying squirrels (Petaurista petaurista), and Sunda colugos (Galeopterus variegatus) with a detailed study on its feeding ecology and behaviour. Night transect surveys were conducted following set, pre-existing paths to assess nocturnal mammal presence and population density. For testing and validating the methodology, night surveys were conducted in Segari Melintang, Perak and Brunei Darussalam.